Experimental investigation on heat transfer characteristics of phase change composite for thermal energy storage system. (2021) - Jidhesh, P.; Arjunan, T.V.; David Rathnaraj, J.
Abstract: A novel technology to produce a low-cost thermal energy storage system using composite phase change materials was presented in this paper. This article examines the enhancement of the charging and discharging rate of the phase change material (PCM). In this paper, paraffin was used as the PCM. The steatite powder was used as the additive material to enhance the thermal property of the PCM. Steatite powder was concentrated in the paraffin at three weight fractions of 10%, 20%, and 30%. The performance of the Paraffin/steatite composite was investigated using a horizontal latent heat energy storage system. The charging and discharging rate during the melting and solidification of the paraffin/steatite composite were studied in detail. From, the experimental analysis, it was observed that as the solidification rate of the PCM increases than the melting rate as the addition of steatite powder in the paraffin increases. This significant effect of increasing rate is mainly due to the property of the steatite material as it has a large latent heat retention rate. From the experimental investigation, it is observed that the solidification rate was improved by about 25%, 37% and 40% than the melting time by adding the low-cost steatite powder in the paraffin with weight fraction 10%, 20%, and 30% respectively. Hereby, this low-cost paraffin/steatite composite was best suited for heating storing applications like solar collector systems.